Odpowiedzi

Najlepsza Odpowiedź!
2010-01-22T15:00:06+01:00

sin x = [√ (8+√15)]/4
sin x = a/r
a= √(8+√15) , r = 4
a² + b² = r²
b² = 16 - a² = 16 - (8+√15) = 8 - √15
b = √(8 -√15)
cos x = b/r = [√(8-√15)]/4
Zatem [sin x + cos x]² = sin²x + cos²x + 2 sin x * cos x =
= 1 + 2 sin x * cos x
Obliczymy teraz 2 sin x *cos x
2 sin x *cos x = 2*{ [√(8 +√15)]/4}*{[√(8 -√15)]/4} =
= [√[(8+√15)(8 -√15)]/ 8 = [ √ (8² -(√15)²)]/8 =
= [√(64 - 15)]/8 = √49 / 8 = 7/8
czyli
[sin x + cos x]² = 1 + 2 sin x * cos x = 1 + 7/8 = 8/8 + 7/8 = 15/8
5 4 5